2021
DOI: 10.1101/2021.04.22.441028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abundance and Microbial Diversity from Surface to Deep Water Layers Over the Rio Grande Rise, South Atlantic

Abstract: Marine microbes control the flux of matter and energy essential for life in the oceans. Until now, the distribution and diversity of planktonic microorganisms above Fe-Mn crusts has received relatively little attention. Future mining\dredging of these minerals is predicted to affect microbial diversity and functioning in the deep sea. Here, we studied the ecology of planktonic microbes among pelagic environments of an Fe-Mn deposit region, at Rio Grande Rise, Southwestern Atlantic Ocean. We investigated microb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Bacteria are predominant in the majority of samples. Many factors contribute to the prokaryote diversity in ocean habitats, such as the availability of organic components and particulate matter, pelagic zones, and depth (Mestre et al, 2017; Ferreira et al, 2022; Walsh et al, 2016). In situ studies of deep-sea bacterioplankton showed the occurrence of bacterioplankton control by seafloor virioplankton, as there was a decrease in bacterial diversity and a change in its structure in the presence of diluted viruses (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria are predominant in the majority of samples. Many factors contribute to the prokaryote diversity in ocean habitats, such as the availability of organic components and particulate matter, pelagic zones, and depth (Mestre et al, 2017; Ferreira et al, 2022; Walsh et al, 2016). In situ studies of deep-sea bacterioplankton showed the occurrence of bacterioplankton control by seafloor virioplankton, as there was a decrease in bacterial diversity and a change in its structure in the presence of diluted viruses (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Water masses are known to have a significant influence on the distribution and composition of coral communities in the Southeast Brazilian continental slope (Arantes et al, 2009;Cavalcanti et al, 2017;Sumida et al, 2004), due to their distinct properties in the water column (temperature, salinity, oxygen, nutrients). In addition, microbial communities from pelagic zones in RGR are structured by water masses (Ferreira et al, 2021). Studies had shown that hexactinellids have high assimilation-to-respiration efficiency for bacteria (Bart et al, 2020), and they are an important functional group that links the pelagic microbial food web to the benthos (Pile and Young, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these similarities, closed circulations above seamounts and internal wave formation may act to trap or provide a mechanism for the downward transport of phytoplankton and particulate organic carbon (POC) (Read and Pollard, 2017;Turnewitsch et al, 2016;Vilas et al, 2009;White et al, 2007). However, RGR is in the oligotrophic South Atlantic Gyre, with a low concentration of organic carbon (Perez et al, 2012) and the main reservoir of new nutrients is trapped below the permanent thermocline, in the South Atlantic Central Water (Ferreira et al, 2021). Physical processes induced by RGR and their biological consequences are unknown and should be investigated in future studies to ascertain which processes are related to the ones driven by seamounts.…”
Section: Discussionmentioning
confidence: 99%
“…Water (Ferreira et al, 2021). Physical processes induced by RGR and their biological consequences are unknown and should be investigated in future studies to ascertain which processes are related to the ones driven by seamounts.…”
Section: Discussionmentioning
confidence: 99%